Seal the deal: An extensive study of European historical copper-based seal matrices using a multimodal protocol. (January 2020) - Castelle, M.; Dillmann, P.; Vega, E.; Blanc-Riehl, C.; Vilain, A.; Chastang, P.; Anheim, E.
Abstract: Seal matrices have been used in many civilizations across the globe for thousands of years. In Europe, during the late medieval and early modern periods, they were made of a resistant material such as metal, frequently copper-based alloys, and were an essential attachment of official documents, serving as personal signatures. By investigating an exceptional body of objects, this work contributes to throw some light on the technical landscape of copper-based seal matrix production which has remained undocumented until now. A multi-modal approach was carried out in order to document the materials and techniques involved. More than four hundred objects were analysed using a recently developed portable XRF protocol for copper-based alloy analysis. In addition, more than one hundred were carefully examined on a micro scale in order to determine the engraving techniques. Cross sections were obtained from six broken seal matrices, allowing the manufacturing process of the objects to be revealed. First, although a wide range of copper-based alloys were documented, namely bronze, red brass and brass, two groups of objects could be identified based on the Pb content, suggesting two levels of quality. Second, three different successive engraving techniques could be identified dating from between the 13th c. and the 17th c: engraving, simple stamp combination and letter punches. Finally, similarities in terms of the fabrication process and the alloys used in French and Italian ways of production could suggest a transborder practice. Apart from providing insights into historical seal matrices production, these results also contribute to the documentation of medieval and early modern copper-based workshops practices. Graphical abstract: Image 1 Highlights: Overview of medieval and early modern European seal matrices technical practices. 466 objects analysed by pXRF in order to document the alloys. Engraving techniques of 142 objects documented using binocular microscopy. 6 cross sections of seal matrices examined under microscope. Crucial information provided on workshops diachronic tradition and specificities.